LED fluorescence microscopy for the diagnosis of pulmonary tuberculosis: a multi-country cross-sectional evaluation. - Luis Eduardo Cuevas (Public Library of Science (PLoS), 2011)
Background The diagnosis of tuberculosis (TB) in resource-limited settings relies on Ziehl-Neelsen (ZN) smear microscopy. LED fluorescence microscopy (LED-FM) has many potential advantages over ZN smear microscopy, but requires evaluation in the field. The aim of this study was to assess the sensitivity/specificity of LED-FM for the diagnosis of pulmonary TB and whether its performance varies with the timing of specimen collection. Methods and findings Adults with cough ≥2 wk were enrolled consecutively in Ethiopia, Nepal, Nigeria, and Yemen. Sputum specimens were examined by ZN smear microscopy and LED-FM and compared with culture as the reference standard. Specimens were collected using a spot-morning-spot (SMS) or spot-spot-morning (SSM) scheme to explore whether the collection of the first two smears at the health care facility (i.e., "on the spot") the first day of consultation followed by a morning sample the next day (SSM) would identify similar numbers of smear-positive patients as smears collected via the SMS scheme (i.e., one on-the-spot-smear the first day, followed by a morning specimen collected at home and a second on-the-spot sample the second day). In total, 529 (21.6%) culture-positive and 1,826 (74.6%) culture-negative patients were enrolled, of which 1,156 (49%) submitted SSM specimens and 1,199 (51%) submitted SMS specimens. Single LED-FM smears had higher sensitivity but lower specificity than single ZN smears. Using two LED-FM or two ZN smears per patient was 72.8% (385/529, 95% CI 68.8%-76.5%) and 65.8% (348/529, 95% CI 61.6%-69.8%) sensitive (p<0.001) and 90.9% (1,660/1,826, 95% CI 89.5%-92.2%) and 98% (1,790/1,826, 95% CI 97.3%-98.6%) specific (p<0.001). Using three LED-FM or three ZN smears per patient was 77% (408/529, 95% CI 73.3%-80.6%) and 70.5% (373/529, 95% CI 66.4%-74.4%, p<0.001) sensitive and 88.1% (95% CI 86.5%-89.6%) and 96.5% (95% CI 96.8%-98.2%, p<0.001) specific. The sensitivity/specificity of ZN smear microscopy and LED-FM did not vary between SMS and SSM. Conclusions LED-FM had higher sensitivity but, in this study, lower specificity than ZN smear microscopy for diagnosis of pulmonary TB. Performance was independent of the scheme used for collecting specimens. The introduction of LED-FM needs to be accompanied by appropriate training, quality management, and monitoring of performance in the field. Trial registration Current Controlled Trials ISRCTN53339491. Please see later in the article for the Editors' Summary.